2020
DOI: 10.1136/vr.105510
|View full text |Cite
|
Sign up to set email alerts
|

Challenging identity: development of a measure of veterinary career motivations

Abstract: BackgroundWhile little is known about the motivations underpinning veterinary work, previous literature has suggested that the main influences on veterinary career choice are early/formative exposure to animals or veterinary role models. The aim of this study was to develop and provisionally validate a veterinary career motivations questionnaire to assess the strength of various types of career motivations in graduating and experienced veterinarians.MethodsA cross-sectional sample of experienced veterinarians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Participants also achieved significant job satisfaction by helping farmers to improve their fertility as they believed they were making their clients better off financially. This is in line with the work of Cake et al ( 46 ) who showed that vets were predominantly motivated to help both animals and people.…”
Section: Discussionsupporting
confidence: 92%
“…Participants also achieved significant job satisfaction by helping farmers to improve their fertility as they believed they were making their clients better off financially. This is in line with the work of Cake et al ( 46 ) who showed that vets were predominantly motivated to help both animals and people.…”
Section: Discussionsupporting
confidence: 92%
“…They seek to continually improve their performance to meet personal standards of excellence 47 48 . The inclusion of items related to motivation in the final VRS–PR aligns with related research identifying intrinsic motivation and the enjoyment of challenging work as important for veterinarians in all stages of their career 23 24 . Motivations related to challenge and learning were amongst the highest rated, most universal and most influential on overall motivation and job satisfaction in that study 24 .…”
Section: Discussionsupporting
confidence: 64%
“…The inclusion of items related to motivation in the final VRS–PR aligns with related research identifying intrinsic motivation and the enjoyment of challenging work as important for veterinarians in all stages of their career 23 24 . Motivations related to challenge and learning were amongst the highest rated, most universal and most influential on overall motivation and job satisfaction in that study 24 . Practitioners low in motivation can reflect on what professional and personal factors may be contributing to this, as well as deliberately focusing on what compelled them to become a veterinarian and what motivates them in their current work 23 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…There is an emerging emphasis on well-being in veterinarians, 1,2 as well as positive aspects of complete mental health more generally. 3 Initial empirical studies have examined aspects of well-being such as motivation, 4,5 self-compassion, 6 mindfulness, 6 meaningfulness, 7 pleasure in work 8 and other personal resources for resilience. 9,10 However, these studies open only a small window into positive mental health states and protective factors in veterinary work.…”
Section: Introductionmentioning
confidence: 99%